Analisis Manajemen Strategi Pemasaran Untuk Meningkatkan Keunggulan Bersaing di Savali Hotel Padang - Doni Muhardiansyah Doni; Rilla Rianty (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
This article aims to discover the ability of company’s strategic management in accomplishing of focusing, positioning and differentiation strategy to pursue its competitiveness. The data were collected through questionnaire, interview, and observation. They analysed by using percentage technique and the qualitative data is analysed by using Miles and Huberman’s analysis technique. The result shows that Savali Hotel does not have enough understanding on niche market focusing strategy. It does not understand the positioning strategy well, so the company’s position is not firmed in the market and the image is not clinging in customers’ mind. It does not have a unique factor compared to other hotels. By using market share analysis that measured through competitor statistic report, it is known that Savali Hotel is in the lowest position compared to the other three hotels. The SWOT analysis’ result shows that Matrix Strategy IE, Matrix Space, and Matrix Grand Strategy of Savali Hotel has opportunities and strength with that good internal condition and has a supportive environment to grab opportunities. In conclusion, the proposed strategy is to support Growth oriented strategy. Some other alternative strategies proposed are intensive and integrative strategy, market penetration strategy, market development, product development, and diversification